Perbandingan Framework Keamanan Siber (NIST CSF, CIS CONTROLS, ISO/IEC 27001, dan COBIT 2019) menggunakan Analytic Hierarchy Process untuk Penguatan Ketahanan Siber TNI - Suhara Golan Sidabutar; I Nengah Putra Apriyanto; Tatar Bonar Silitonga; Priyanto Priyanto (Dinamik, 2026)
The escalation of global cyber threats, including ransomware, data breaches, and Advanced Persistent Threats, requires defence organizations to adopt measurable cybersecurity frameworks that are aligned with operational needs. This article compares four cybersecurity frameworks, namely the NIST Cybersecurity Framework (CSF), CIS Critical Security Controls, ISO/IEC 27001, and COBIT 2019, to determine the most appropriate alternative for strengthening the cyber resilience of the Indonesian National Armed Forces (TNI). The study employs a descriptive-comparative design with a quantitative approach based on the Analytic Hierarchy Process (AHP). Expert judgments are collected through pairwise comparisons across the criteria of governance, risk management, operational and technical controls, compliance and certification, implementability, and cost. The synthesis of priority weights indicates that NIST CSF obtains the highest priority, particularly in the risk management dimension. The findings also underline the need to adapt NIST CSF to the military context, including confidentiality requirements, response speed, and integration with doctrine and operational procedures.